PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA AUDIO VISUAL TERHADAP PENGETAHUAN REMAJA PUTRI TENTANG PEMERIKSAAN PAYUDARA SENDIRI (SADARI): THE INFLUENCE OF HEALTH EDUCATION WITH AUDIO VISUAL MEDIA TO THE KNOWLEDGE OF TEENAGE GIRLS ABOUT BREAST SELF-EXAMINATION (BSE) - Lestari, R. Tri Rahyuning; Laksmi, i Gusti Ayu Satya; Sintari, Silvia Ni Nyoman (Bali Medika Jurnal, 2019)
Introduction : Breast Cancer is a desease with high incidence rate in many countries and has high risk of dead if it handled late. Breast Self-Examination (BSE) can be performed to detect breast cancer symptoms early so it can reduce the risk of death. The goal of the research is to know more about the the influence of health education with audio visual media to the knowledge of young women about breast self-examination (BSE) in SMAN 1 Kuta Utara. Method: The method of this research is pre experimental design with one group pre-post test design. The sample of this research is 33 students selected using purposive sampling technique. The measurement of student’s knowledge in pre test is 17 person (51,5%) have a less knowledge and 16 person (48,5%) have an enough knowledge. The post test result is 20 person (60,6%) have a good knowledge and 13 person (39,4%) have an enough knowledge. Discussion: This is because of the sutend have already get the intervention form of give the information through the health education with audio visual media about BSE.